Legal Analysis Regarding the Dismissal of Judges During Their Term of Office - Dewangga, Andi; Firmantoro, Zuhad Aji (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2024)
This research examines the legal analysis regarding the mechanism for the dismissal of Constitutional Judge Aswanto by the People's Representative Council (DPR) before the end of his term of office, highlighting challenges to the integrity and independence of the Indonesian Constitutional Court (MK). In the context of appointing and dismissing judges involving the DPR, Supreme Court, and President, the research uses an empirical juridical approach to explore the interaction between legal norms applicable practices, and public perceptions. This research method combines normative analysis of regulations with in-depth interviews and public surveys. The findings show that Justice Aswanto's dismissal was influenced more by politics than a clear violation of the law, raising concerns about political interference threatening the MK's independence. A dismissal process that lacks transparency and objectivity raises serious questions about the integrity of the legal process. This research recommends reforms in the judge removal mechanism to reduce political influence and ensure a fairer and more transparent process and emphasizes the importance of public oversight and participation to strengthen public trust and maintain the integrity of the judiciary.